Harmonising Science and Religion in the Life of Generation Z in Indonesia: Efforts Towards Social and Cultural Integration: Harmonisasi Sains dan Agama dalam Kehidupan Generasi Z di Indonesia: Upaya Menuju Integrasi Sosial dan Budaya - Marchella Dika Aristawidya (Averroes: Journal for Science and Religious Studies, 2024)
Research  Background: This research focuses on how Generation Z in Indonesia integrates science and religion in their lives, seeing this phenomenon as a reflection of significant social and cultural shifts. Method: Using an analytical descriptive methodology, this research examines the interaction between science and religion through the lens of younger generations in Indonesia, considering the influence of education and social media. The main findings: Generation Z tends to approach science and religion in a more integrated and inclusive manner, exploring and accepting both domains as part of a holistic understanding of the world. Contribution: a deepened understanding of how younger generations can reconcile different perspectives on science and religion, directing educational policy to support a more coherent approach. The research suggests the importance of education that supports intellectual openness and cultural tolerance as a way to facilitate better integration between science and religion, not only in academic contexts but also in everyday life. Conclusion: Generation Z, with its openness and critical ability, has the potential to be an agent of change in harmonising science and religion.